LONGTERM CHANGES OF SOLAR ACTIVITY ASYMMETRY - Leiko, U. M. (Одеські астрономічні публікації, 2016)
We report results of analysis of the northsouth asymmetry of solar activity, solar magnetic fields. The analysis is based on the sunspot data, 1875–2015 (http://solarscience.msfc.nasa.gov/greenwch.shtml), largescale solar magnetic field (solar mean magnetic field, SMMF) and solar polar magnetic field time series, 1975– 2015 (http://wso.stanford.edu). To study long-term changes of solar activity asymmetry we applied analysis of cumulative sum. Cumulative sum averages shortperiodic changes and identifies long-term periodicity. Minimum of cumulative sum of sunspot area mean monthly values time series occurs in ~1910, maximum – in ~1980. Perhaps this is branch growth of long-term (~140-years) cycle of solar activity asymmetry. Cumulative sums of polar magnetic field of different pole have ~22-years periodicity. Change of cumulative sum of SMMF time series has different character. But long-run trend with intervals of positive and (or) negative polarity of ~22 years is observed.